2010
DOI: 10.1007/s10336-010-0527-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weather and climate variation on Hoopoe reproductive ecology and population growth

Abstract: Preserving peripheral populations is a key conservation issue because of the adaptive potential to environmental change they provide for the species as a whole. Yet, peripheral populations are often small and isolated, i.e. more vulnerable to stochastic events and prone to extinction. We studied a peripheral population of Hoopoe (Upupa epops), a rare insectivorous farmland bird, in the Swiss Alps. We first investigated the effect of weather variation on food provisioning to chicks by Hoopoe parents. Second, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 40 publications
(50 reference statements)
6
83
1
3
Order By: Relevance
“…High local precipitation during the breeding season is typically associated with low breeding success in Central Europe [33]–[35]. Additionally, precipitation may affect dispersal, with breeding dispersal (dispersal from one breeding site to another) becoming lower with higher breeding success [20], [36], [37].…”
Section: Methodsmentioning
confidence: 99%
“…High local precipitation during the breeding season is typically associated with low breeding success in Central Europe [33]–[35]. Additionally, precipitation may affect dispersal, with breeding dispersal (dispersal from one breeding site to another) becoming lower with higher breeding success [20], [36], [37].…”
Section: Methodsmentioning
confidence: 99%
“…Nestling mortality is mainly due to starvation (Lack 1956, O'Connor 1979, which, in turn, is related to inclement weather conditions (Lack & Lack 1951, Gory 1987, Cucco et al 1992, Thomson et al 1996. Being aerial feeders, Common Swifts are particularly sensitive to meteorological conditions because both their foraging success and the availability of invertebrate prey can be severely affected by adverse weather (Avery & Krebs 1984, Arlettaz et al 2010. Indeed, adults can prolong incubation during periods of bad weather (Cramp 1998), and age at fledging strongly depends on weather conditions (Hudec 1983).…”
Section: Weather Conditions Brood Size and Hatching Order Affect Commentioning
confidence: 99%
“…Although previous studies have shown that changing food supply often has an effect on energy expenditure and breeding success or chick growth rates (Brinkhof and Cavé 1997; Zanette et al 2003; Both 2010; Barichello and Mossop 2011; te Marvelde et al 2011), few studies have shown this relationship in passerines through direct measures of both fledgling production and food abundance. The availability of invertebrate prey and the profitability of avian foraging on them can be higher at higher temperatures (e.g., Avery and Krebs 1984; Arlettaz et al 2012), but especially so for aerial insectivores (Veistola and Lehikoinen 1997). The problem of food measurement for these species that take flying insect prey from the air is made easier by the availability of suction samplers that produce representative samples of available prey at frequent intervals, but this guild of consumers has the parallel challenge that day-to-day fluctuations in air temperatures are associated with dramatic variations in food supply (Hails and Bryant 1979; Emlen et al 1991; McCarty 1995).…”
Section: Introductionmentioning
confidence: 99%